Border poetics - Lundberg, Liv (Nordlit, 2014)
The language of poetry is a language of inquiry, not the language of a genre. Poetry has the capacity of entering those zones known as borderlands, where you meet strange things and foreign people. In this poetic world view, the border is not an edge along the fringe of lands, societies and experiences, but rather their very middle – and their in-between. The structures of language are social structures in which meanings and intentions are already in place, always fighting for power and dominance, with rhetorical figures and more violent weapons.